PERAN ORANG TUA DALAM MEMBIMBING BELAJAR AL-QUR’AN PADA MASA PANDEMI COVID-19 - Nur Qomari; Ahmad Fauzi (LP3M IAI Al-Qolam, 2021)
COVID-19 has become a very scary thing. Due to the corona virus, many victims have fallen. To avoid the spread of the virus, the government made various efforts and decisive actions that must be obeyed by the community. This also had an impact on the school life, including at MTs. Nurul Hidayah. The students who initially always received Al-Qur'an tutoring before lessons started, the activity is closed during the pandemic. Therefore, the role of parents in Al-Qur'an learning is needed during the pandemic. This research focuses on the role of parents during the corona pandemic in guiding the learning of the Qur'an for class VIII students in the odd semester of the 2020-2021 in Simojayan, Ampelgading, Malang. This is a field research with qualitative descriptive approach. The data sources used are secondary and primary obtained from collection techniques in the form of observations, interviews, and documentation. The research got the following results: The interest in learning the Qur'an of VI students during the COVID-19 pandemic in the 2020-2021 Academic Year in the Odd semester is in a good spirit level, as evidenced by the data that from 33 students, 6 children are enthusiastic in learning the Koran, 24 children have a good level of enthusiasm and 3 others are less enthusiastic in learning Al-Qu`an. When children are more concerned about playing with their peers, they ignore the words of their parents to recite Al-Qu`an.